Recent population differentiation in the habitat specialist Glossy Antshrike (Aves: Thamnophilidae) across Amazonian seasonally flooded forests - Silva, Sofia Marques; Ribas, Camila Cherem; Aleixo, Alexandre (Ecology and Evolution, 2021)
We assessed population structure and the spatio-temporal pattern of diversification in the Glossy Antshrike Sakesphorus luctuosus (Aves, Thamnophilidae) to understand the processes shaping the evolutionary history of Amazonian floodplains and address unresolved taxonomic controversies surrounding its species limits. By targeting ultraconserved elements (UCEs) from 32 specimens of S. luctuosus, we identified independent lineages and estimated their differentiation, divergence times, and migration rates. We also estimated current and past demographic histories for each recovered lineage. We found evidence confirming that S. luctuosus consists of a single species, comprising at least four populations, with some highly admixed individuals and overall similar levels of migration between populations. We confirmed the differentiation of the Araguaia River basin population (S. l. araguayae) and gathered circumstantial evidence indicating that the taxon S. hagmanni may represent a highly introgressed population between three distinct phylogroups of S. luctuosus. Divergences between populations occurred during the last 1.2 mya. Signs of population expansions were detected for populations attributed to subspecies S. l. luctuosus, but not for the S. l. araguayae population. Our results support that S. luctuosus has had a complex population history, resulting from a high dependence on southeastern “clear water” seasonally flooded habitats and their availability through time. Spatial and demographic expansions toward the western “white water” flooded forests might be related to recent changes in connectivity and availability of these habitats. Our study reinforces the view that isolation due to absence of suitable habitat has been an important driver of population differentiation within Amazonian flooded forests, but also that differences between várzeas (“white water” floodplains, mostly in southwestern Amazonia) and igapós (“clear water” floodplains, especially located in the east) should be further explored as drivers of micro-evolution for terrestrial species. © 2021 The Authors. Ecology and Evolution published by John Wiley & Sons Ltd.
Keywords: Igapó; Phylogeography; population genomics; Sakesphorus luctuosus; taxonomy; ultraconserved elements; Várzea